2D Seismic Structural and Stratigraphic Study of Kirkuk Group Formation in Amara Oil Field- Southeastern Iraq - Jaheed, Ali K.; Karim, Hussein H. (Iraqi Journal of Science, 2021)
The Amarah Oil field structure was studied and interpreted by using 2-D seismic data obtained from the Oil Exploration company. The study is concerned with Maysan Group Formation (Kirkuk Group) which is located in southeastern Iraq and belongs to the Tertiary Age. Two reflectors were detected based on synthetic seismograms and well logs (top and bottom Missan Group). Structural maps were derived from seismic reflection interpretations to obtain the location and direction of the sedimentary basin. Two-way time and depth maps were conducted depending on the structural interpretation of the picked reflectors to show several structural features. These included three types of closures, namely two anticlines extended in the directions of S-SW and NE, one nose structure (anticline) in the middle of the study area, and structural faults in the northeastern part of the area, which is consistent with the general fault pattern. The seismic interpretation showed the presence of some stratigraphic features. Stratigraphic trap at the eastern part of the field, along with other phenomena, such as flatspot (mound), lenses, onlap, and toplap, were detected as indications of potential hydrocarbon accumulation in the region.